Survival in renal replacement therapies within a concept integral offer services in Peru, from 2008 to 2012 - Cieza Zevallos , Javier (2013)
Objective: To describe the effect on survival and quality of life of patients with End-stage renal disease (ESRD) in various renal replacement therapies (RRT) admitted to a public financing program in Peru (SIS). Materials and Methods: A retrospective cohort longitudinal study of ESRD patients on hemodialysis (HD), peritoneal dialysis (PD) and renal transplantation (RT) between 2008 to 2012, in a SIS program. Results: There were 175 patients starting RRT. Overall survival was 95.1%, 91.3% and 87.9% for first, second and third year respectively. Cox multivariate analysis showed that the only variables that influenced survival were sex (men > women) and age ( ≥ 60 years, lower survival < 60). The quality of life at the end of the study (Karnofsky < 60 and / or deceased vs. Karnofsky ≥ 60 and alive), was only related to age (50 years) and type of RRT. Conclusions: The survival rate of patients in this program funded by the SIS program is comparable to any local or foreign series and only depends on age and sex. The quality of life was higher in those admitted with age <50 years and those undergoing RT.